Comparison of quality of life between pre- and post-operative standard laparoscopic cholecystectomy using Short Form-36 - Nikhil Nakhate,; Neeraj Kumar Banoria,; Pankaj Saunakiya,; Nalin Kumar,; Jatin Chauhan,; Shibin Geroge, (Asian Journal of Medical Sciences, 2024)
Background: Gallstone disease (cholelithiasis) is a wide spectrum of conditions, ranging from asymptomatic cholelithiasis, biliary colic, empyema gallbladder, and gangrene to perforation and peritonitis. Aims and Objectives: The aim of this study was to assess the quality of life before and after a standard laparoscopic cholecystectomy (LC) using the Short Form-36 (SF-36). Materials and Methods: In the study cohort of 100 patients using SF-36 in patients of pre-operative and post-operative standard LC are compared in eight domains of health quality index in Maharani Laxmi Bai Medical College, Jhansi between January 2021 and June 2022. Results: There is finding of significant change in seven domains in mean±1 month, (1) Physical functioning – pre-operative and post-operative, that is, 33.00±31.812 and 88.68±22.40, respectively, (2) Role limitations due to physical health – pre-operative and post-operative, that is, 3.5±18.401 and 98.75±10.546, respectively, (3) Role limitations due to emotional problems – pre-operative and post-operative, that is, 4.67±21.128 and 98.67±11.489, respectively, (4) Energy/fatigue- pre-operative and post-operative, that is, 34.94±16.638 and 83.11±12.456, respectively, (5) Social pre-operative functioning – pre-operative and post-operative, that is, 39.38±20.428 and 98.88±5.196 respectively, (6) Pain – pre-operative and post-operative, that is, 34.73±18.340 and 97.30±15.489, respectively, (7) General health – pre-operative and post-operative, that is, 35.85±35.897 and 67.00±35.511, respectively, and minimal change in one domain (8) Emotional well-being – pre-operative and post-operative, that is, 34.16±15.491 and 39.08±18.694. Conclusion: The pre-operative and post-operative parameters of the SF-36 questionnaire show a significant change in their mean±standard deviation at 1-month postoperatively following standard LC. The maximum significant change occurred in parameters of physical functioning, role emotion, role physical, energy, social functioning, pain, and general health.